Overview of halal freshwater aquaculture system: Malaysian perspectives - Muflih, Betania Kartika; Parson, Sitti Walida; Kassim, Zaleha; Chowdhury, Ahmed Jalal Khan (Zibeline International Publishing, 2022)
In line with the increasing halal demand around the world, one of the sectors that attract the halal world attention is the freshwater aquaculture for fish food. The demand goes higher day by day as the marine catch start to deplete and world needs an alternative to suffice the demand for protein supply. This paper discusses the overview of current freshwater scenario in Malaysia and reported issues regarding the depreciation of halal of freshwater fish exposed by media for the last few years up until the recent time. The issue of water pollution which is synonymous in freshwater aquaculture activity is also briefly discussed. Moreover, this paper also outlines the potential issue that is often overseen even by the farm operator in order to obtain the halal farm certified. Solution is also given in this paper by proposing the application of halal block chain technology in freshwater aquaculture sector. The methodology used is mainly the library research from various reliable sources, such as database and search engine that cover selected journals and information regarding the subject matters, including references from local or international fisheries authorities. Expert views focusing on block chain technology through article writing in mass media are also taken as a reference. The discussion in this paper hopefully can provide a clearer view on the reality of issues faced by the freshwater fish aquaculture sector as well as provide a good potential solution by the application of disruptive technology of block chain system in accordance with the government recommendations in Industrial Revolution 4.0.